Microbial and pigment profile of the reddish patch occurring within Tuber magnatum ascomata. Issue 12 (December 2018) - Amicucci, Antonella; Barbieri, Elena; Sparvoli, Valentina; Gioacchini, Anna Maria; Calcabrini, Cinzia; Palma, Francesco; Stocchi, Vilberto; Zambonelli, Alessandra
Abstract: Tuber magnatum Pico, the delectable white truffle, is the most prized truffle species. In this study, we examined the reddish pigmentation that frequently occurs in T . magnatum ascomata for the presence of pigment-producing bacteria. The inner part of the reddish-pigmented region of three T . magnatum ascomata collected in North–Central Italy was analysed. This reddish part was used to establish a bacterial culture collection and to extract the total genomic DNA in order to obtain a library of 16S rRNA genes representative of the bacterial community. The molecular approach revealed limited microbial diversity within the reddish-pigmented regions compared to the wider range of bacterial species commonly found at the same maturation stage and season in T . magnatum ascomata. The pigmented regions showed a prevalence of specific bacterial species belonging to α-, β- and γ- Proteobacteria, Actinobacteria and Firmicutes . From the tandem mass spectrometry analysis of the extracted pigment, four compounds were identified: i) bixin, ii) β-carotene, iii) cis-1-glycosyl-apo-8′- lycopene and iv) the fucoxanthin. Carotenoid producing species such as Microbacterium and Chryseobacterium emerged as the most likely cause of the peculiar reddish pigment production. Indeed, our findings suggest that the peculiar reddish pigment might be produced by these bacterial species. Highlights: The cause of the formation of red patches in Tuber magnatum ascomata, the most valuable truffles, was investigated. Carotenoid spectra found in the reddish patch of truffles were analysed. Bacterial species associated with the reddish patch that were capable of producing carotenoid pigments were identified.